Expression of Physaria longchain acyl-CoA synthetases and hydroxy fatty acid accumulation in transgenic Arabidopsis - Bengtsson, Jesse D (Journal of plant physiology, 2022)
Copyright © 2022 Elsevier GmbH. All rights reserved.